2007
DOI: 10.1080/08927010601137856
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial materials research applied to the development of new surface coatings IV. A high-throughput bacterial biofilm retention and retraction assay for screening fouling-release performance of coatings

Abstract: A high-throughput bacterial biofilm retention screening method has been augmented to facilitate the rapid analysis and down-selection of fouling-release coatings for identification of promising candidates. Coatings were cast in modified 24-well tissue culture plates and inoculated with the marine bacterium Cytophaga lytica for attachment and biofilm growth. Biofilms retained after rinsing with deionised water were dried at ambient laboratory conditions. During the drying process, retained biofilms retracted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…Using a systematic, combinatorial and high-throughput approach [110], the effect of key compositional variables such as siloxane composition and polyol composition on the surface and bulk properties of the coating are being explored [111][112][113][114]. Rapid laboratory bioassays have also been developed to permit the screening of large numbers of coating samples in an efficient time frame [115,116]. Using this approach, coating compositions have been identified that have a combination of excellent release properties, stability in water, good adhesion and high bulk modulus, and are candidates for field testing.…”
Section: Siloxane-urethane Hybrid Systemsmentioning
confidence: 99%
“…Using a systematic, combinatorial and high-throughput approach [110], the effect of key compositional variables such as siloxane composition and polyol composition on the surface and bulk properties of the coating are being explored [111][112][113][114]. Rapid laboratory bioassays have also been developed to permit the screening of large numbers of coating samples in an efficient time frame [115,116]. Using this approach, coating compositions have been identified that have a combination of excellent release properties, stability in water, good adhesion and high bulk modulus, and are candidates for field testing.…”
Section: Siloxane-urethane Hybrid Systemsmentioning
confidence: 99%
“…For some coatings it has been found that marine bacteria may retract from the surface of the coating and this has been correlated to the release performance of marine organisms from the coating surface. [144,149,150] These highthroughput methods have been used to screen a number of different candidate polymer and coatings compositions for their performance in the marine environment. [151][152][153][154][155][156] In addition, this workflow has also been used to study the structure-property relationships of UV-cured coatings [157] and for the exploration of hybrid organic-inorganic coatings.…”
Section: Applications Of Combinatorial and High-throughput Experimentmentioning
confidence: 99%
“…For example, the automated water jet apparatus was developed for screening of a range of potential foulingrelease coatings that were deposited in multiwell plates [17,34,35,37,39]. A water channel apparatus with fully calibrated turbulent flow was also used to quantify the fouling-release potential of coatings [32,36].…”
Section: Introductionmentioning
confidence: 99%